The tipping point: fateful moments in child protection. (24th August 2015) - Kettle, Martin
Abstract: Social workers working to protect children face the prospect of making very finely balanced judgements, often on the basis of incomplete information. Based on doctoral research into sense‐making by social workers, this paper explores aspects of the tipping point, i.e. where the categorization of a child's situation changes, potentially leading to a very different response to their needs. Those aspects include identifying the triggers for, and consequences of, the tipping point, and being aware that the tipping point being reached may have to do with changes in the internal world of the worker as well as changes in the circumstances of the family. This paper stresses the need for a more nuanced understanding of the tipping point, and emphasizes the need to take account of the processes of decision‐making, and of looking at both inter‐ and intra‐personal components of those processes. Further, it is argued that a cautious attitude requires to be taken towards technical–rational solutions and that there is a real need to place professional judgement and consideration of the tacit dimension at the heart of the child protection process.